Analisis Faktor yang Berpengaruh dalam Pengambilan Keputusan Investasi pada Mahasiswa Akuntansi UPN “Veteran” Jawa Timur - Devina Setya Vanessa; Muslimin (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This study aims to test data and prove the influence of mental accounting, financial literacy, and risk perception on investment decisions of accounting students at the Universitas Pembangunan Nasional